Test of Active Compound and Activity Pirdot Leaf Extract (Sauraia Vulcani Korth.) on Candida Albicans Growth in Vitro - Marbun, Romauli Anna Teresia (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: to determine the activity of pirdot leaf extract on the growth of Candida albicans in vitro Design: this study was a true experiment with a post-test only control group research design. The method used agar diffusion using Kirby Bauer technique. This study used 4 variations concentration namely 10%, 20%, 40%, and 80%, positive control (ketoconazole tablets), and negative control (Dimethyl Sulfoxide). The data obtained were analyzed using descriptive statistical analysis. Interventions: the intervened variable were compound content and antifungal activity of pirdot leaf extract concentration of inhibitory effect. Main outcome measures: the main measurement in this study was the inhibition concentration of pirdot leaf extract on Candida albicans growth Results: the results showed that the inhibitory from a concentration of 10% of 8.96 mm, the highest inhibition was at 80% of 18.33 mm. Conclusion: it could be concluded that pirdot leaf extract has antifungal activity against Candida albicans. Keywords: Antifungal; Candida albicans; Diffusison Method; Saurauia vulcani Korth